PERTUMBUHAN DAN HASIL SAWI (Brassica juncea) DENGAN KOMBINASI BAHAN ORGANIK BERBAHAN AMPAS TEBU PADA DUA PERIODE TANAM - Dia Novita Sari; Yudi Gustian; Edi Susilo (PUCUK : Jurnal Ilmu Tanaman, 2021)
Mustard greens is a type of leaf vegetable that is favored by consumers because it contains high levels of pro-vitamin A and ascorbic acid which are beneficial for health. However, the production of mustard greens is still relatively low due to the limited availability of fertilizers. Bagasse is the first waste produced from the industrial processing of sugar cane, the volume reaches 30 - 34% of milled sugar cane. This research was conducted in the experimental field of Ratu Samban University. The purpose of this study was to determine the growth and yield of mustard greens against a combination of organic matter made from bagasse in two planting periods. This study used a single factor Completely Randomized Block Design (RAKL) with 10 replications. The treatment used in this study consisted of 4 levels, namely: P0 = control without treatment, P1 = 200g bagasse + 75g chicken manure, P2 = 250g bagasse + 50g chicken manure, P3 = 300g bagasse + 25g chicken manure. The results showed that the planting of the first and second periods, all treatments, namely P0, P1, P2, P3 had a very significant effect on all observation variables at all plant ages. P3 treatment (300g bagasse + 25g chicken manure) gave the best results on all variables observed yotu plant height, number of leaves, plant production, shoot wet weight, and root wet weight.